2021
DOI: 10.1128/msphere.00862-20
|View full text |Cite
|
Sign up to set email alerts
|

The Fifth International Neonatal and Maternal Immunization Symposium (INMIS 2019): Securing Protection for the Next Generation

Abstract: Despite significant progress in reaching some milestones of the United Nations Sustainable Development Goals, neonatal and early infant morbidity and mortality remain high, and maternal health remains suboptimal in many countries. Novel and improved preventative strategies with the potential to benefit pregnant women and their infants are needed, with maternal and neonatal immunization representing effective approaches. Experts from immunology, vaccinology, infectious diseases, clinicians, industry, public hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The development of protective and therapeutic treatment options is an ongoing challenge, but many promising strategies are currently being investigated. Presently, antibody supplementation therapy seems to be the closest to being a successful clinically applicable treatment, either in the form of maternal vaccination or mAbs ( 83 ). While maternal vaccination currently is the best strategy for term-born neonates, preterm neonates may benefit most from innovative antibody therapies, especially intravenous immunoglobulin G enriched with IgM and IgA, and modified synthetic polyvalent immunoglobulins ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…The development of protective and therapeutic treatment options is an ongoing challenge, but many promising strategies are currently being investigated. Presently, antibody supplementation therapy seems to be the closest to being a successful clinically applicable treatment, either in the form of maternal vaccination or mAbs ( 83 ). While maternal vaccination currently is the best strategy for term-born neonates, preterm neonates may benefit most from innovative antibody therapies, especially intravenous immunoglobulin G enriched with IgM and IgA, and modified synthetic polyvalent immunoglobulins ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the failure of post-septic treatment research to date, it would be beneficial to establish preventive methods in addition to elucidating the pathophysiology of neonatal sepsis. Some specific preventive approaches have been proposed to positively modify the immune response of neonates, including vaccination or limited exposure to non-infectious components of bacteria that are recognized by the innate immune system [12]. In recent years, it has been reported that certain infectious conditions and vaccinations induce a wide range of protective effects against other pathogens through the innate immune system, a characteristic known as "trained immunity" [13].…”
Section: Introductionmentioning
confidence: 99%